Bulk photochromism in a tungstate-phosphate glass: A new optical memory material? - Poirier, Gael; Nalin, Marcelo [UNESP]; Cescato, Lucila; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (American Institute of Physics (AIP), 2006)
In this work, we present a new photochromic tungstate based glass which have both absorption coefficient and refractive index modified under laser exposure. The photosensitive effect is superficial under ultraviolet (UV) irradiation but occurs in the entire volume of the glass under visible irradiation. The effect can be obtained in any specific point inside the volume using an infrared femtosecond laser. In addition, the photosensitive phenomenon can be erased by specific heat treatment. This glass can be useful to substitute actual data storage supports and is a promising material for 3-dimensional (3D) and holographic optical storage.